Computational Collective Intelligence. Technologies and Applications Second International Conference, ICCCI 2010, Kaohsiung, Taiwan, November 10-12, 2010. Proceedings, Part III - Pan, Jeng-Shyang; Chen, Shyi-Ming; Nguyen, Ngoc-Thanh (Lecture Notes in Artificial Intelligence, 2010)
This volume composes the proceedings of the Second International Conference on Computational Collective Intelligence--Technologies and Applications (ICCCI 2010), which was hosted by National Kaohsiung University of Applied Sciences and Wroclaw University of Technology, and was held in Kaohsiung City on November 10-12, 2010. ICCCI 2010 was technically co-sponsored by Shenzhen Graduate School of Harbin Institute of Technology, the Tainan Chapter of the IEEE Signal Processing Society, the Taiwan Association for Web Intelligence Consortium and the Taiwanese Association for Consumer Electronics. It aimed to bring together researchers, engineers and po- cymakers to discuss the related techniques, to exchange research ideas, and to make friends. ICCCI 2010 focused on the following themes: • Agent Theory and Application • Cognitive Modeling of Agent Systems • Computational Collective Intelligence • Computer Vision • Computational Intelligence • Hybrid Systems • Intelligent Image Processing • Information Hiding • Machine Learning • Social Networks • Web Intelligence and Interaction Around 500 papers were submitted to ICCCI 2010 and each paper was reviewed by at least two referees. The referees were from universities and industrial organizations. 155 papers were accepted for the final technical program. Four plenary talks were kindly offered by: Gary G. Yen (Oklahoma State University, USA), on "Population Control in Evolutionary Multi-objective Optimization Algorithm," Chin-Chen Chang (Feng Chia University, Taiwan), on "Applying De-clustering Concept to Information Hiding," Qinyu Zhang (Harbin Institute of Technology, China), on "Cognitive Radio Networks and Its Applications," and Lakhmi C.